Current trends in the zonal distribution and asymmetry of ozone in Antarctica based on satellite measurements - Ruixian Yu; Volodymyr Reshetnyk; Asen Grytsai; Gennadi Milinevsky; Oleksandr Evtushevsky; Andrew Klekociuk; Yu Shi (Ukrainian Antarctic Journal, 2024)
The development of the Antarctic ozone hole in late winter and spring (September–November) is the most noticeable phenomenon in the polar stratosphere. It has appeared every season since the early 1980s within the stratospheric polar vortex, preventing air mass from mixing with middle latitudes and affecting the distribution of minor atmospheric constituents, including ozone. The ozone hole strongly depends on dynamic factors, mainly planetary wave propagation from the troposphere to the stratosphere. This study aims to identify the total ozone longitudinal distribution for austral spring and individual months, September, October, and November, and consider the observed trends in detail. We provide an analysis to retrieve trends in total ozone during the development of the ozone hole. Time averaging of the total ozone longitudinal distribution was performed using the three-month ozone means in the austral spring. This procedure eliminates fluctuations and impacts of traveling waves. The latitudinal range of 55–80°S was analyzed to characterize the total ozone distribution in the ozone hole edge and inner regions. Distributions for individual months (September, October, and November) were considered to describe the observed trends in detail. The analysis of the obtained results indicates a close-to-linear negative total ozone trend during the ozone hole intensification (the 1980s–early 1990s). This trend was determined at all the analyzed latitudes, with total ozone decreasing by 150 DU during 15 years in the zonal longitudinal minimum region. However, the analysis of the trends shows that ozone layer recovery is not observed in the Antarctic spring, taking into account low ozone levels in 2020–2023. No clear trends were noted after the period of decline, but the October values in zonal maximum have slightly decreased in the last decade. The zonal minimum has drifted eastward during the decline in total ozone, but the subsequent time range shows large interannual changes without any significant long-term tendency in both maximum and minimum longitudes.